Exploring the human hair follicle microbiome. (1st May 2021) - Lousada, M.B.; Lachnit, T.; Edelkamp, J.; Rouillé, T.; Ajdic, D.; Uchida, Y.; Di Nardo, A.; Bosch, T.C.G.; Paus, R.
Summary: Human hair follicles (HFs) carry complex microbial communities that differ from the skin surface microbiota. This likely reflects that the HF epithelium differs from the epidermal barrier in that it provides a moist, less acidic, and relatively ultraviolet light‐protected environment, part of which is immune‐privileged, thus facilitating microbial survival. Here we review the current understanding of the human HF microbiome and its potential physiological and pathological functions, including in folliculitis, acne vulgaris, hidradenitis suppurativa, alopecia areata and cicatricial alopecias. While reviewing the main human HF bacteria (such as Propionibacteria, Corynebacteria, Staphylococci and Streptococci), viruses, fungi and parasites as human HF microbiome constituents, we advocate a broad view of the HF as an integral part of the human holobiont. Specifically, we explore how the human HF may manage its microbiome via the regulated production of antimicrobial peptides (such as cathelicidin, psoriasin, RNAse7 and dermcidin) by HF keratinocytes, how the microbiome may impact on cytokine and chemokine release from the HF, and examine hair growth‐modulatory effects of antibiotics, and ask whether the microbiome affects hair growth in turn. We highlight major open questions and potential novel approaches to the management of hair diseases by targeting the HF microbiome.